Evolusi Institusi Pendidikan Islam Klasik : Masjid, Kuttab dan Madrasah - Suwanto; Jahrul Sihotang; Anisah Sari Lubis; Solihah Titin Sumanti; Yusnaili Budianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islam has the ability to adapt to various existing places and situations without being contaminated. Mosques are an important component in classical Islamic education. On the other hand, Kuttab is a pre-Islamic educational institution which is a form of adaptation and modification of Muslims to the old heritage. Then Kuttab experienced significant development as a respectable and dignified educational institution. The universality of Islam is also demonstrated through non-Muslim kuttab teachers, without questioning Islam which is an important part of the kuttab institution. The purpose of this article is to describe the existence of mosques as the original form of early Islamic educational institutions which were the forerunners of the emergence of Kuttab and madrasa educational institutions. By answering the various questions above through in-depth analysis and interpretation, it is hoped that this article can become a reference for finding out significant changes to education in mosques, kuttabs and madrasas. This article uses a type of qualitative research with a study approach (library research). The analysis used is by using the Miles & Huberman interaction model. What this article produces is the historical development of Islamic education, social changes in education in mosques which gave rise to kuttab institutions and madrasah institutions.